Essence and system of measures of administrative law enforcement - Chupris, Olga I. (Journal of the Belarusian State University. Law, 2019)
In the article the conclusion is drawn that the administrative law enforcement is used not only in connection with the imposition of administrative sanctions (measures of administrative responsibility, administrative remedial measures, measures to ensure the administrative process), but also in connection with the implementation of public administration (administrative warning measures, measures of administrative legal restraint, administrative remedial measures). The article traces discrepancies between the essence of the measure and its legal provision and the order of its application. This shows that some of the legal relations are not regulated by law enforcement norms, and that the uncertainty in the legal regulation do occur.